Pediatric reference intervals of free thyroxine and thyroid stimulating hormone in three different hospitals - ÇİLİNGİRTÜRK, AHMET METE (WALTER DE GRUYTER GMBH, 2018)
Objective: Using data retrieved from three different hospitals, we established indirect reference intervals of free thyroxine (FT4) and thyroid stimulating hormone (TSH) for the Centaur XP or the Immulite 2000 instruments, in separate reference limits at each subset. Methods: We categorized children into seven age groups: 4-7 days, 8-15 days, 16-23 days, 24-61 days, 3-6 months, 7-36 months and 4-6 years. After a Box-Cox transformation was employed, we followed the Horn algorithm to eliminate the extreme values. Results: The remaining FT4 (11,230) and TSH (11,274) tests were statistically analyzed. We determined separate reference limits at each subset with their own 2.5th and 97.5th percentiles. The interaction effect of both hospital and age grouping on FT4 was meaningful, but there was no interaction effect on TSH. Conclusions: Pediatric FT4 and TSH test results should be interpreted via narrowed age groups, especially in the first 3 weeks of neonatal period. Our reference limits may be recommended in pediatric follow-ups, considering the conditions of prematurity, birth-weight or multiple births. Preanalytical and analytical variations related with complex molecular structure of FT4 should be taken into consideration to ensure the validity of the result.
Keywords: Immunoassays; pediatric reference intervals; hospital information system; thyroid stimulating hormone; thyroxine; UNIFORM REFERENCE INTERVAL; CONGENITAL HYPOTHYROIDISM; BIOCHEMICAL MARKERS; REFERENCE RANGES; SERUM THYROXINE; FUNCTION TESTS; FREE T-3; CHILDREN; INFANTS; TRIIODOTHYRONINE